IMPLEMENTASI PENGUATAN KEPUTUSAN MENTERI AGAMA NOMOR 447 TAHUN 2015 TENTANG LIMA NILAI BUDAYA KEMENTERIAN AGAMA DALAM MENGANTISIPASI PERNIKAHAN SIRI DI KANTOR KUA MEDAN BELAWAN - Ramadhan Syahmedi Siregar, Ilham Maulana, Nispul Khoiri, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstrak: The purpose of this study was to determine the implementation of the strengthening of the decree of the Minister of Religion number 447 2015 about the five cultural values of the Ministry of Religion in anticipating a series of marriages at the Medan Belawan KUA office, how to implement the strengthening, inhibiting and supporting factors as well as evaluating and solving them. This study uses a qualitative method. This research is located in the center of Medan Belawan religious affairs office. Data collection techniques using documentation, interviews and observations. Data analysis techniques using data collection, data reduction, data presentation and conclusions. Research informants here are Medan Belawan KUA, Belawan Medan MUI, Religious Leaders and Medan Religious Affairs Ministry. The results showed that the implementation of the strengthening of the decree of the minister of religion number 447 2015 about the five cultural values of the ministry of religion in anticipating siri marriage at the Medan Belawan KUA office was in terms of its implementation using work culture, service culture and transformative culture. The supporting factor is because the facilities and infrastructure provided by the ministry of religion (in this case the Medan ministry of religion) are very supportive especially for those who use online-based marriage registration. Material understanding about the importance of sakinah families that have been recorded through BP4 Ministry of Religion of North Sumatra Province. While from the obstacle aspect due to the lack of awareness of some people the community will join the Sakinah family program. Evaluation and solution by conducting counseling-registration of marriages and happy families, sakinah families, independent families, family planning, harmonious families conducted by the advisory body, marriage guidance and preservation (BP4) in the Office of religious affairs to prospective brides and guardians. Meanwhile, in terms of evaluation, Medan Belawan KUA conducts evaluation based on Sumative evaluation, Formative evaluation and diagnostic evaluation.Keywords: Implementation, Regulation of the Minister of Religion, FiveCultural Values, Ministry of Religion